Thinking Low-Tech: promoting local practices in design studio - Kristanti Dewi Paramita,; andi Andri Yatmo, (Penerbit Universiti Kebangsaan Malaysia, 2023)
This article interrogates low-tech material and construction as the basis of pedagogical strategies in the architectural design studio, enabling the development of innovative spatial interventions which foster dialogues between humans and their environment. The high-tech, contemporary architectural design movement generates limitless possibilities of architecture driven by technological advancement. Nevertheless, it is argued that the notion of low-tech enables the rediscovery of architecture that is rooted in its context, driven by the human-centred integration between natural resources and local material practices. Focusing on low-tech also provides the opportunity to develop meaningful innovation within the scope of the rural environment, a context often omitted within the urban-laden academic discourse. This article outlines lessons learned from the exploration of low-tech in a third-year architectural design studio at Universitas Indonesia. The studio begins by creating the collective compilation of vernacular knowledge in the techniques of gathering, treating, and crafting the material in their respective context. The design process follows by exploring the low-tech assembly of these materials in context, defining the needed passive manoeuvres to generate the appropriate spatial qualities. In conclusion, the compilation of material expands knowledge on materiality within a tropical context, where the material is found and transformed through connection with nature, appropriation of time, and intersection with communities’ lifecycles. The low-tech assembly exploration expands ways of conscious reading towards the environment, both globally and from a more localised perspective. Such conscious reading enables students to programmatically develop the position and configuration of their project as a whole, thus enriching the pedagogical strategies of passive architectural design.